1996
DOI: 10.1037/0894-4105.10.4.588
|View full text |Cite
|
Sign up to set email alerts
|

Validating a cognitive ability testing protocol with Lao children for community development applications.

Abstract: The emergence of the sociocultural perspective in cross-cultural psychology has discouraged the adaptation of standardized tests in nonindustrialized settings. Yet, cognitive assessments are needed for monitoring the effects of nutritional, health, and educational interventions. Forty-seven Lao children 5 to 12 years of age completed the Kaufman Assessment Battery for Children (K-ABC), the Tactual Performance Test (TPT), and the computerized Tests of Variables of Attention (TOVA). TPT performance measures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Notwithstanding recent research attempts to address specific properties of select CPTs (Boivin et al, 1996;Forbes, 1998;Llorente et al, 2001;and Losier, McGrath, & Klein, 1996), limited information is available in the literature, particularly for clinical groups with neuropsychological deficits including ADHD, related to the internal properties of these procedures. Despite these limitations, CPTs continue to be used to assess ADHD symptomatology.…”
mentioning
confidence: 97%
“…Notwithstanding recent research attempts to address specific properties of select CPTs (Boivin et al, 1996;Forbes, 1998;Llorente et al, 2001;and Losier, McGrath, & Klein, 1996), limited information is available in the literature, particularly for clinical groups with neuropsychological deficits including ADHD, related to the internal properties of these procedures. Despite these limitations, CPTs continue to be used to assess ADHD symptomatology.…”
mentioning
confidence: 97%
“…The visual form of the TOVA, a computer-based, continuous performance test that assesses basic constructs of attention, 15 was performed as tested in several other crosscultural settings. 4,16 TOVA scores assessed included omission error rates, commission error rates, correct signal response time variability, and the d′ signal detection measure (signal detection sensitivity). The TPT, part of the Reitan-Indiana neuropsychological assessment battery for children, 17 was performed as tested previously among rural African children.…”
Section: Cognitive Testingmentioning
confidence: 99%
“…Using exploratory factor analyses, it was found that the crosscultural equivalence of the underlying structure was high. The K-ABC (the predecessor of the KABC-II), based on the sequential versus simultaneous processing distinction, was applied in many non-Western countries (e.g., Boivin et al, 1996;Conant et al, 1999;Jansen & Greenop, 2008;MardellCzudnowski, 1995). Holding et al (2004) and Moon et al (2003) found the underlying model to be present in adapted versions in Kenya and Korea, respectively.…”
Section: Generalizability Of Cognitive Structurementioning
confidence: 99%